Dendritic cell-intrinsic Ezh2 expression maintains thymic homeostasis and prevents premature thymic involution - Sint Thida Bo (Nanyang Technological University, 2023)
Ezh2, a well-known histone methyltransferase, was previously shown to regulate the integrin-dependent migration of dendritic cells (DCs) via the non-canonical cytosolic methylation of the cytoskeleton protein Talin. It remained unclear if Ezh2 has other functional roles in DCs. Here, we found that DC-intrinsic Ezh2 regulated the early T cell development in an age-dependent manner. In adult mice, DC-intrinsic Ezh2 deficiency led to a decreased thymic cellularity with a developmental block at DN2-DN3 stages, possibly due to a weak Notch signaling as the downstream targets of Notch were downregulated. Interestingly, although there was an overall decreased cellularity, γδ T cells and CD8+ T cells increased significantly. The thymic architecture was disrupted, and the cytokine milieu showed an inflammatory signature. These phenotypes suggest that DC-intrinsic Ezh2 deficiency caused an accelerated thymic involution. Ezh2-deficient cDC1 showed an upregulation of proteins involved in cross-presentation pathway while cDC2 showed an activated and inflammatory phenotype. Interestingly, Ezh2 deletion reduced the H3K27me3 level in cDC1 but not in cDC2 and pDC, suggesting that Ezh2 regulates the functions of DCs in a cell type specific manner via both canonical and non-canonical mechanisms. The ablation of cDC1 was able to partially restore the CD8+ and γδ T cell bias while the ablation of pDC did not change the phenotypes in mice with Ezh2-deficient DCs. While thymic DCs are generally known to present self-antigens to mediate the negative selection of self-reactive thymocytes, our study reveals their unexpected involvement in mediating the early stages of T cell development and thymic involution. The reduction in T cell output due to thymic involution is one of the main contributors to the increased susceptibility of old individuals to cancer, infections, and autoimmunity. Our study sheds light on the previously underappreciated role of dendritic cells in mediating thymic involution and may bring us one step closer to finding the elixir of life.